Health-related behavior and quality of life among the elderly: a population-based study - Margareth Guimarães Lima; Marilisa Berti de Azevedo Barros; Chester Luiz Galvão César; Moisés Goldbaum; Luana Carandina; Maria Cecília Goi Porto Alves (Universidade de São Paulo, 2011)
OBJECTIVE: To assess the association between health-related behaviors and quality of life among the elderly. METHODS: A population-based cross-sectional study was carried out including 1,958 elderly living in four areas in the state of São Paulo, southeastern Brazil, 2001/2002. Quality of life was assessed using the Medical Outcomes Study SF-36-Item Short Form Health Survey instrument. This instrument's eight subscales and two components were the dependent variables. Independent variables were physical activity, weekly frequency of alcohol consumption and smoking. Multiple linear regression models were used to control for the effect of gender, age, schooling, work, area of residence and number of chronic conditions. RESULTS: Physical activity was positively associated with the eight SF-36 subscales. The stronger associations were found for role-physical (β=11.9), physical functioning (β=11.3) and physical component. Elderly individuals who consumed alcohol at least once a week showed a better quality of life than those did not consume alcohol. Compared to non-smokers, smokers had a poorer quality of life for the mental component (β=-2.4). CONCLUSIONS: The study results showed that physical activity, moderate alcohol consumption and no smoking are positively associated with a better quality of life in the elderly.